2013
DOI: 10.1021/ez4000862
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Perfluorooctanoic Acid by Reactive Species Generated through Catalyzed H2O2 Propagation Reactions

Abstract: Perfluorinated compounds, which are environmentally persistent and bioaccumulative contaminants, cannot currently be treated in the subsurface by in situ technologies. Catalyzed H 2 O 2 propagation (CHP) reactions, which generate hydroxyl radical, hydroperoxide anion, and superoxide anion, were investigated for treating perfluorooctanoic acid (PFOA) as a basis for in situ chemical oxidation remediation of groundwater. Using 1 M H 2 O 2 and 0.5 mM iron(III), PFOA was degraded by 89% within 150 min. Hydroxyl rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
91
3
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(98 citation statements)
references
References 36 publications
2
91
3
2
Order By: Relevance
“…These intermediates are strong oxidizing species able to mineralize organic compounds [37,38]. However, an extensive debate on the oxidative pathway of PFOA exists nowadays, because it has been demonstrated that ·OH radicals generated by Fenton reagent are not very effective in the PFOA mineralization [30,39] and that Ti IV OH· + can take an active part in the mineralization reaction [27,40,41].…”
mentioning
confidence: 99%
“…These intermediates are strong oxidizing species able to mineralize organic compounds [37,38]. However, an extensive debate on the oxidative pathway of PFOA exists nowadays, because it has been demonstrated that ·OH radicals generated by Fenton reagent are not very effective in the PFOA mineralization [30,39] and that Ti IV OH· + can take an active part in the mineralization reaction [27,40,41].…”
mentioning
confidence: 99%
“…This is true in the case of the remediation of PFASs [12]. The fluoro-carbon skeletons is so stable that it can resist the attack of •HO [28]. However, the EAOP has been proven to be an effective method for breaking down PFASs.…”
Section: Aop /Eaopmentioning
confidence: 99%
“…As said, there are various degradation approaches [12], for example Fenton reaction of hydrogen peroxide [28], persulphate [12], chemical oxidation [56], sonolytic conversion [57], etc. This review focuses on EAOP [58] that is summarised in Table 2.…”
Section: Degradation Of Pfassmentioning
confidence: 99%
See 1 more Smart Citation
“…For direct photolysis, the electrophilic oxidants are oxygen in the reaction solution or water molecules of the reaction solution (Niu et al, 2013;Gatto et al, 2015;Mitchell et al, 2013). The C 6 F 13 C 16 O 18 O and C 6 F 13 C 18 O 18 O are the main intermediates resulting from direct irradiation of PFOA in H 2 18 O solutions under high oxygen pressure (Hori et al, 2004a).…”
Section: Mechanism Of Pfoa Degradationmentioning
confidence: 99%